Thermal hydrolysis of poly(l‐lactic acid) films and cytotoxicity of water‐soluble degradation products. Issue 25 (12th March 2015) - Xu, Guoguang; Liu, Xiao; Lin, Yanqun; He, Guoshan; Wang, Wanjuan; Xiong, Wen; Luo, Haiying; Liu, Zhong; Zhao, Jianhao
ABSTRACT In this study, the thermal hydrolysis of the poly(l‐lactic acid) (PLLA) films was investigated for its potential use as a food‐packaging ecomaterial. The surface morphology, mass loss, molecular weight, thermal properties, and medium pH were routinely investigated; meanwhile, in particular, the composition and cytotoxicity of the water‐soluble degradation products were studied. The changes in the mass loss and molecular weight revealed a random chain‐scission mechanism. Differential scanning calorimetry analysis implied that the hydrolysis preferentially took place in the amorphous region. The medium pH decreased with time because of the accumulation of acid water‐soluble products in the medium. Liquid chromatography/mass spectrometry analysis proved that these products were composed of 1–13 lactic acid units, in which the content of l‐lactic acid increased with time and reached 9.71 mmol/L after hydrolysis for 84 days. The in vitro cell culture indicated that the water‐soluble degradation products from the PLLA films had no cytotoxicity to human umbilical vein endothelial cells. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42064.